Spatial epidemiological analysis of American foulbrood outbreaks over the past 18 years in Turkiye - Bayir, Tuba; Uslu, Ugur (Univ Zagreb Vet Faculty, 2025)
American foulbrood (AFB), a highly infectious and fatal disease of honey bees, is caused by Paenibacillus larvae. Despite its beekeeping and economic importance, little is known about the historical epidemiology and geographical distribution of AFB in bees. The aim of this study was to evaluate AFB clusters across Turkiye, and to see how the cluster model has changed. In this study, a retrospective analysis of AFB epidemiology in Turkiye was performed, using data from outbreaks registered with the World Organisation for Animal Health (WOAH-OIE) between 2005 and 2022. Descriptive statistical analyses were performed to evaluate the number of outbreaks and cases by region, month, year and season. Spatial statistical tests (Local Moran's I and Getis-Ord Gi*) were used to locate potential AFB epidemiological clusters, and cartographic maps were produced. During the 18-year period, 403 outbreaks and 18,483 cases were recorded. The results of this study showed an irregular trend in the spread of AFB over the period studied. The results of this study show that the highest number of outbreaks and cases were detected in summer and spring, with rates of 30.77% and 37.46% respectively. The majority of outbreaks and cases were recorded in the Black Sea Region. Moran's statistics showed a positive spatial autocorrelation in AFB cases across the country for 2008-2010 and 2014-2016. The results of this study can contribute to our understanding of the spatial epidemiology of the disease, and provide policy makers with useful data for surveillance activities.
Prostorna epidemiološka analiza izbijanja ameri?ke gnjilo?e u proteklih 18 godina u Turskoj
Keywords: American foulbrood; honey bee colony; paenibacillus larvae; spatial analysis; Turkiye